A mixed‐method study on gender and intrahousehold differences in food consumption from Khatlon Province, Tajikistan - Pechtl, Sarah M. L.; Mardonova, Mohru; Ergasheva, Tanzila; Lambrecht, Isabel B. (Wiley, 2026)
Tajikistan faces significant food insecurity and multiple forms of malnutrition in its population, with women particularly at risk. Social norms related to gender and intrahousehold hierarchy are pervasive. Yet, how gender impacts dietary intake in Tajikistan remains to be studied. Understanding this mechanism is critical to develop adequate strategies for effective, equitable progress in mitigating malnutrition and food insecurity. An explanatory sequential mixed-methods study was conducted to assess the extent and identify the drivers of gender-based and intrahousehold differences in dietary diversity in Khatlon Province, Tajikistan. Predictors of dietary diversity were statistically assessed using quantitative survey data from 1704 adults who participated in the 2023 USAID/IFPRI Population-Based Survey. Qualitative data from 12 focus group discussions, 19 individual interviews, and 21 Photovoice interviews were analyzed using reflexive thematic analysis to further ascertain and understand these drivers. Gender was identified as a predictor of dietary diversity in both quantitative and qualitative findings. Women reported lower dietary diversity than men, even within in the same household. Gender norms contribute to unequal food distribution and opportunities to consume food away from the household. Expressing social values such as respect during mealtimes and perceptions of dietary needs prioritize men and children over women in consuming foods deemed more nutritious (e.g., meat). This study highlights the importance of considering household dynamics and gender roles in equitably addressing food and nutrition insecurity and malnutrition. Mitigating malnutrition in Tajikistan will necessitate gender equity-focused social behavior change interventions targeting women and men across different generations.